A 7‐day team‐based model of care in general medicine: implementation and outcomes at 12 months. Issue 1 (27th January 2016) - Gilfillan, C.; Newnham, E.; Nagappan, R.; Evans, J.; Compton, J.
Abstract: Background: Demand for inpatient beds is increasing whilst supply is diminishing. General medical services are feeling this demand as the ageing population presents more patients with undifferentiated illness traditionally cared for by this service. Redesign efforts need to focus on improving the quality and speed of decision‐making to utilise resources efficiently. Aims: The aim of this study was to improve patient flow through general medical services by undertaking a comprehensive redesign process targeting each stage of the patient journey. Methods: We utilised a rapid improvement event to identify waste and design a new model of care (MOC) that eliminated as much waste as possible. The model had three main elements: (i) ward‐based teams; (ii) 7‐day per week standard work; and (iii) pull systems to operate for all transfers and referrals. Here, we analyse the first 12 months of the new MOC with regard to key outcomes: length of stay, occupancy, weekend discharges, clinical incidents and Medical Emergency Team (MET) calls, emergency department length of stay and National Emergency Access Target (NEAT) performance and elective surgical throughput. Results: The new MOC resulted in a 0.88‐day reduction in length of stay. This resulted in reduced general medical bed occupancy of 19 beds. Weekend discharges improved by 54.6%. There were no significant increases in serious clinical incidents or MET calls. Emergency department admitted NEAT performance improved also. Conclusion: Redesign of the general medicine model of care eliminating waste has resulted in a significant improvement in patient flow and reduced length of stay without compromising quality of care.